USING HOMOPHONE GAMES TO IMPROVE PRONUNCIATION FOR HIGH SCHOOL STUDENT - Harsin Harsin; Rifiqoh Rifiqoh; Mashuri Mashuri (e-Journal of ELTS (English Language Teaching Society), 2022)
The objective of this research is to prove that the use of homophone games can improve pronunciation of the eleventh grade students at SMKN 1 Sojol. This research applied pre-experimental research design. The sample of this research was 21 eleventh grade students of ATPH 1 (Agribisnis Tanaman Pangan dan Horticultura) as known as Agriculture major, consisting of 21 students. The sample was selected by using a purposive sampling technique. The data were collected by administering a pronunciation test conducted before and after treatment, called pre-test and post-test. The result of pre-test and post-test shows that the mean score of pre-test is 34.44, and the mean score of post-test is 76.19. The result of data is analyzed statically by applying t-test formula. The result of data analysis shows that the value of the t-counted is(4.30) was higher than the t-table value (1.725) by applying 0.05 level of significance and 20 degree of freedom (df) 21-1 =20. The implication of this finding is to the betterment of teaching pronunciation is that the teacher needs to use Homophone Games to improve students’ pronunciation.